2021
DOI: 10.1007/s11356-021-14037-8
|View full text |Cite
|
Sign up to set email alerts
|

First application of an Integrated Biological Response index to assess the ecotoxicological status of honeybees from rural and urban areas

Abstract: Understanding the effects of environmental contaminants on honeybees is essential to minimize their impacts on these important pollinating insects. The aim of this study was to assess the ecotoxicological status of honeybees in environments undergoing different anthropic pressure: a wood (reference site), an orchard, an agricultural area, and an urban site, using a multi-biomarker approach. To synthetically represent the ecotoxicological status of the honeybees, the responses of the single biomarkers were inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 101 publications
(124 reference statements)
1
6
0
Order By: Relevance
“…We can consider the modulation obtained and the effects known in literature for bees and other organisms to justify our results and to compare the stressors. The inhibition of AChE activity in the highly stressed site is in line with the results of [71] where bees collected from agricultural areas shoved a reduction of AChe activity. However, it is strange that the same inhibition was not evidenced in the chemical-stress site.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We can consider the modulation obtained and the effects known in literature for bees and other organisms to justify our results and to compare the stressors. The inhibition of AChE activity in the highly stressed site is in line with the results of [71] where bees collected from agricultural areas shoved a reduction of AChe activity. However, it is strange that the same inhibition was not evidenced in the chemical-stress site.…”
Section: Discussionsupporting
confidence: 86%
“…The use of a battery of biomarkers on two life stages (pupae and worker bees) allowed the study of these parameters in "stress conditions" (exposure sites) but also in "physiological conditions" (control site). In the literature, biomarkers were already used to test different stresses (urban pollution and pesticides) on Apis mellifera both in the field [67][68][69][70][71][72] and in laboratory [73][74][75]. In the field, a reference station is always chosen away from anthropogenic sources but close enough to the experimental sites to have a direct comparison [68][69][70]74].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also observed a neurotoxic effect positively correlated to alterations in the feeding behavior of O. bicornis. Caliani et al (2021b) found a neurotoxic effect of Amistar® Xtra (a.i., azoxystrobin), but no data were produced regarding syrup consumption. The inhibitory effect on the AChE activity by tebuconazole, related with immobility, has been also reported in aquatic organisms (Altenhofen et al 2017;Lebrun et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The AChE activity was assayed in the head extracts according to Ellman et al (1961) with modification from Caliani et al (2021b). The reaction mixture was prepared in a 3-mL cuvette and contained 0.1 M sodium phosphate buffer (pH 7.4), 10 mM DTNB, 41.5 mM acetylthiocholine, and 5 μL head extract.…”
Section: Achementioning
confidence: 99%
See 1 more Smart Citation